2012
DOI: 10.1016/j.ijge.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities on the Outcomes of Older Patients Receiving Rectal Cancer Surgery

Abstract: s u m m a r yBackground: The decision to perform surgery on older patients often presents as an ethical dilemma. The purpose of this study is to investigate the impact of comorbidities on the clinical outcomes of older rectal cancer surgery patients, with the goal of enabling healthcare professionals to evaluate the risk of surgery for the treatment of cancer in older patients with comorbid chronic disease. Methods: This study included 320 patients >60 years of age who were treated from 2004e2009 at a medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(27 reference statements)
1
3
0
1
Order By: Relevance
“…With respect to case covariates age, sex and comorbidities like coagulopathies, heart diseases, lung diseases or fluid and electrolyte disorders were risk factors for poor patient outcome in both groups in this analysis, which is supported by the literature as well 26 43–48…”
Section: Discussionsupporting
confidence: 80%
“…With respect to case covariates age, sex and comorbidities like coagulopathies, heart diseases, lung diseases or fluid and electrolyte disorders were risk factors for poor patient outcome in both groups in this analysis, which is supported by the literature as well 26 43–48…”
Section: Discussionsupporting
confidence: 80%
“…Research involving cancer survivors with multimorbidity has shown variable relationships between multimorbidity and cancer outcomes including overall survival [16][17][18][19][20][21][22], treatment complications [23,24], and lower likelihood of guideline-concordant care [25][26][27]. Some studies also suggest significantly lower HRQOL among multimorbid survivors [28][29][30], but few studies have explored individual comorbidities and their associations with specific HRQOL outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy plus radiotherapy has revealed itself as a potential application as part of a new therapeutic trend in treating locally advanced cervical cancer patients 29 . Older patients with comorbidities are at a higher risk of in-hospital complications following rectal cancer surgery, whereas the presence of comorbidities did not show a significant adverse effect on 1-year mortality 30 , and a history of hypertension, diabetes, cardiovascular disease, or cerebrovascular disease was not a significant predictor of 1-year mortality.…”
Section: Discussionmentioning
confidence: 77%